MUC501 : Music technology for composer / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
Music Technology is designed to introduce students to digital music world through the use of digital audio workstation. In this project-based course, students experience technology through hands-on activities, such as MIDI sequencing on piano roll editor, creating humanized MIDI, simple audio editing, applying DSP effects and automation, and eventually working on track-by-track music mix. Besides the final project, students work on short assignments to demonstrate an understanding of practical hardware and software implementation. This is a prerequisite course prior to Jingle Production and Film Scoring where students will equip themselves with essential knowledge to work with digital audio and MIDI on their own computers and even at recording studio.